Reverberații ale caragialismului în eseistica lui Andrei Pleșu (I) - Ilie, Loredana Nicoleta (Studia Romanica Posnaniensia, 2023)
The first part of the article with the title Reverberations of Caragialism in Andrei Pleșu’s essays, completes the effort of systematizing the Caragialian literary legacy, by adding to the post-Caragialian literary corpus the publicistic essays written by Andrei Pleșu. In volumes such as Faces and masks of transition (Chipuri și măști ale tranziției), Comèdies at the gates of the Orient (Comèdii la porțile Orientului), The public obscenity (Obscenitatea publică), we find sufficient evidence of Andrei Pleṣu’s belonging to the literary trend of Caragialism. In this first part of the article, we point out that essential components from the paradigm of Caragialism, such as the irony and the sarcasm, the politics, the parade patriotism and the gastronomy are alluded to and revalued in Andrei Pleșu’s essays, in a way that highlights both the viability of the model and Pleșu’s endowment with an exceptional humoristic talent and satirical sense, worthy of a literary follower of I.L. Caragiale.